The power of a positive attitude : your road to success - Fritz, Roger (New Delhi : Fingerprint, 2019)
Why you need this book -- The gift of a great attitude -- The power of your attitude -- The power of thoughts: your thoughts shape your identity -- The power of words: your words become your reality -- The power of actions : your actions determine your character -- The power of habits: your habits predict your future -- The power of choice: your choices change your life -- Choices with the power to transform your life -- Believe it will all work out: hope -- Don't take yourself too seriously: humility -- Count your blessings: gratitude -- Give more than you take: generosity -- Be kind to everyone you meet: compassion -- Celebrate life: joy -- Keep going no matter what: perseverance -- Becoming a positive person -- Rebooting your brain for a positive outlook -- Leveraging the mind-body connection -- Becoming a positive influence -- You can!
Keywords: Attitude (Psychology) -- Religious aspects -- Christianity